COVID-19 Associated Ocular manifestation; Presented in tertiary hospital Hyderabad. - Khanzada, Mehtab; Sultan, Sharjeel; Gilal, Imtiaz Ahmed; Hyder, Ghulam; Leeza, Mona; Shakeel, Ayisha (Journal of Liaquat University of Medical & Health Sciences, 2021)
OBJECTIVE: To explore the COVID-19 associated ocular manifestation in subjects visited tertiary hospital Hyderabad-Pakistan. METHODOLOGY: This observational prospective study was conducted at the Institute of Ophthalmology, Liaquat University Medical and Health Sciences (LUMHS) Jamshoro from August 2020 to January 2021. All subjects’ ages range from 18 to 65 years visiting the out-patient eye department and/ or admitted to the emergency ward of LUMHS Jamshoro having a positive nasopharyngeal PCR for COVID-19 with and without ocular signs and symptoms were included. The questionnaire proforma was designed to obtain related information. Social sciences of the statistical package, SPSS 22 version was used for results analysis. RESULTS: Out of one hundred and eleven subjects, forty-nine (44.1%) subjects with ocular symptoms and Sixty-two (55.8%) without ocular symptoms had a fever and 7(14.2%) and 17(27.4%) had prior ocular history, respectively. Conjunctival secretion (57.1%) was found the most common abnormality of ocular surface manifestation followed by pain, redness, and burning sensation. Applying univariate analysis general characteristics exposed that gender, age, fever, ocular prior history, ventilation mechanical, state of disposition, and markers of inflammation were not associated significantly with ocular symptoms. CONCLUSION: Conjunctival secretion was found the most common abnormality of ocular surface manifestation associated with COVID-19 infection. The increasing proportion of ocular COVID-19 signs and symptoms cannot be ignored. To obtain better outcomes, prompt and aggressive eye management is still necessary. KEYWORDS: COVID 19; ocular manifestations; signs and symptoms; inflammatory markers.